Metabolic Insights into Iron Deposition in Relapsing-Remitting Multiple Sclerosis via 7 T Magnetic Resonance Spectroscopic Imaging - Alexandra Lipka; Wolfgang Bogner; Assunta Dal-Bianco; Gilbert J. Hangel; Paulus S. Rommer; Bernhard Strasser; Stanislav Motyka; Lukas Hingerl; Thomas Berger; Fritz Leutmezer; Stephan Gruber; Siegfried Trattnig; et al. (NeuroImage: Clinical, 2023)
Objective: To investigate the metabolic pattern of different types of iron accumulation in multiple sclerosis (MS) lesions, and compare metabolic alterations within and at the periphery of lesions and newly emerging lesions in vivo according to iron deposition. Methods: 7 T MR spectroscopic imaging and susceptibility-weighted imaging was performed in 31 patients with relapsing-remitting MS (16 female/15 male; mean age, 36.9 ± 10.3 years). Mean metabolic ratios of four neuro-metabolites were calculated for regions of interest (ROI) of normal appearing white matter (NAWM), “non-iron” (lesion without iron accumulation on SWI), and three distinct types of iron-laden lesions (“rim”: distinct rim-shaped iron accumulation; “area”: iron deposition across the entire lesions; “transition”: transition between “area” and “rim” accumulation shape), and for lesion layers of “non-iron” and “rim” lesions. Furthermore, newly emerging “non-iron” and “iron” lesions were compared longitudinally, as measured before their appearance and one year later. Results: Thirty-nine of 75 iron-containing lesions showed no distinct paramagnetic rim. Of these, “area” lesions exhibited a 65% higher mIns/tNAA (p = 0.035) than “rim” lesions. Comparing lesion layers of both “non-iron” and “rim” lesions, a steeper metabolic gradient of mIns/tNAA (“non-iron” +15%, “rim” +40%) and tNAA/tCr (“non-iron” −15%, “rim” −35%) was found in “iron” lesions, with the lesion core showing +22% higher mIns/tNAA (p = 0.005) and –23% lower tNAA/tCr (p = 0.048) in “iron” compared to “non-iron” lesions. In newly emerging lesions, 18 of 39 showed iron accumulation, with the drop in tNAA/tCr after lesion formation remaining significantly lower compared to pre-lesional tissue over time in “iron” lesions (year 0: p = 0.013, year 1: p = 0.041) as opposed to “non-iron” lesions (year 0: p = 0.022, year 1: p = 0.231). Conclusion: 7 T MRSI allows in vivo characterization of different iron accumulation types each presenting with a distinct metabolic profile. Furthermore, the larger extent of neuronal damage in lesions with a distinct iron rim was reconfirmed via reduced tNAA/tCr concentrations, but with metabolic differences in lesion development between (non)-iron-containing lesions. This highlights the ability of MRSI to further investigate different types of iron accumulation and suggests possible implications for disease monitoring.